Analysing the laws on eviction of squatters in Malaysia / Nur 'Izzah Azhani Khairill Anwar, Nurfilzah Ahmad Jaafar and Nurul Izzah Jannah Mohd Rasidi - Khairill Anwar, Nur 'Izzah Azhani; Ahmad Jaafar, Nurfilzah; Mohd Rasidi, Nurul Izzah Jannah (2013)
The issue of squatters is not to be considered as isolated matter in Malaysia, as observations and studies have identified numerous social issues and problems to derive from it. Steps and measures taken by the government and the authorities in charge seem to change nothing but little damages to eradicate this problem. There is an undeniable urgent need to address squatters' issues fairly and equitably as they may also be part of the underprivileged masses where the government has a major role to play in addressing their problems. However, most incidents and cases that had happened show that the law does not recognize at all any act of squatting, as the act is also baseless in equity. As it is an offence under the Malaysian law, it has not been treated as social or social-economic problem. The harsh law and the fact that these squatters are not being attended as they should have been is most probably the major reason of why this matter is still an issue in our country. Thus in the end of the research, we proposed for the laws to be amended where appropriate, that is, by recommending for the reconstruction in terms of the procedure of eviction of squatters and the welfare system in Malaysia, revamping the housing policy and amending the law of forced eviction of squatters and lastly for the act of squatters to be criminalized, to be more precise. These are to provide a balance between the rights derived from the existing land law applied in Malaysia and the humanitarian point of view. A balance between these two would fill in the gaps and lacunae that exist in our law.